Love: recognising relationships in work with vulnerable youth - Hilde Marie Thrana (Scottish Journal of Residential Child Care)
The article focuses on the role love can play in professional child welfare services (CWS). It is based on participant observation and interviews with 14 young people in contact with the CWS in Norway. The youths are followed from a time when they were rebelling and in conflict with the environment through their experiences of entering into a partnership with social workers supporting them in their school, work, family and leisure. The youths' perspectives on what love is in professional relationships is discussed in light of Axel Honneth's theory of recognition, where love can be seen as a foundation for the development of identity and self-esteem. The article finally discusses what love can bring to social work practices and, specifically, to work with vulnerable youth.